2013
DOI: 10.1159/000348732
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Multidisciplinary Childhood Obesity Treatment Intervention on Adipocytokines, Inflammatory and Growth Mediators

Abstract: Background/Aims: To examine the effects of a 3-month multidisciplinary intervention on anthropometric measures, physical activity patterns and fitness, inflammatory cytokines, adipocytokines, and growth mediators in obese children. Methods: 21 obese subjects completed the 3-month intervention and were compared with 20 age-, gender- and maturity-matched controls. Subjects underwent anthropometric measurements (weight, height, BMI percentile and waist circumference), blood tests (IL-6, CRP, leptin, adiponectin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0
9

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 25 publications
3
34
0
9
Order By: Relevance
“…Similarly, exercise-induced reduction in CRP was not independent of changes in body composition [28]. This effect may depend on age, however, since among young women such an exercise-initiated decrease in CRP was independent of changes in body composition [25], and among children, the changes in CRP were not related to changes in body composition [26]. The interactive effects of fitness and fatness on CRP may also be more complicated as the effect appears to be larger among obese participants [25] and among more fit participants [28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, exercise-induced reduction in CRP was not independent of changes in body composition [28]. This effect may depend on age, however, since among young women such an exercise-initiated decrease in CRP was independent of changes in body composition [25], and among children, the changes in CRP were not related to changes in body composition [26]. The interactive effects of fitness and fatness on CRP may also be more complicated as the effect appears to be larger among obese participants [25] and among more fit participants [28].…”
Section: Discussionmentioning
confidence: 99%
“…To further complicate this issue, the interactive effects may depend upon the age of the population studied as the independent relation of fitness to CRP appears less evident in children [12,14,16,17,23], which might be because CRP reflects chronic systematic low-grade inflammation that emerges over time [16]. Some intervention studies indicate that a decrease in CRP after an exercise intervention is dependent upon body mass or fat loss [21,24], others report that the effects of exercise are independent of changes in fatness and fitness [25], or even that changes in CRP are related to changes in physical activity and not body composition [26]. Not many intervention studies have investigated the fitness fatness interaction specifically and almost all of them have been conducted in middle-aged or older adults [20,27,28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, changes in adiponectin correlated negatively with changes in HOMA and body fat percentage, only in the CT, and baseline and postintervention adiponectin levels did not differ between them [99]. The independent role of PE, besides anthropometric improvements, in raising adiponectin levels has also been highlighted [100].…”
Section: Interventional Studies and Adiponectin Levelsmentioning
confidence: 93%
“…Among these studies, Gong et al [19], Roberts et al [20], Rynders et al [21], Izadpanah et al [22], Garanty-Bogacka et al [23], Martos Moreno et al [24], Balagopal et al [25] and Gallistl et al [26] showed similar change in IL-6 levels after decrease of BMI. On the other side, Nemet et al [27], Roth et al [28], and Amati et al [29] found no significant change. D' Adamo et al [30] recently demonstrated a significant increase of esRAGE in obese children after life style intervention combined with Vitamin E supplementation.…”
Section: Discussionmentioning
confidence: 93%